Artificial intelligence: Explainability, ethical issues and bias - Alaa Marshan (Annals of Robotics and Automation - Peertechz Publications, 2021)
There is no doubt that Artificial Intelligence (AI) is a topic that is attracting increasing attention from different communities, business and academic. AI adoption and implementation is faced by the difficulty of interpreting and trusting the outcomes of AI algorithms. Several ethical issues related to AI adoption such as algorithms and data bias are among the factors that hinder AI adoption by the business world. This study aims to highlight and classify the most important research that have been published on AI explainability and ethical issues. The main finding from this research refer to the necessity of forming proper comprehension of advantages and disadvantages offered by Explainable AI techniques. This work concludes that the interpretability of AI models needs to be investigated using innovative approaches such as data visualisation in conjunction with the requirements and constraints associated with data confidentiality and bias as well as the auditability, fairness and accountability of the AI model.